Conectando cidade e campo: o papel dos mercados digitais na construção de sistemas alimentares sustentáveis no Rio de Janeiro - Júlia Izecksohn; Ève Anne Bühler (Confins)
The paper discusses the role that digital commerce can play in the construction of more sustainable food commercialization circuits that promote, among other aspects, (re)connections, both between spaces and between agents involved in the food system. Faced with the strong commercial concentration exercised by supermarkets and the difficulties for products and agents that promote alternative food systems to access the market, we seek to understand how digital commerce can be mobilized to build more sustainable supply networks and to what extent these networks are able to implement more environmentally and socially responsible principles. We sought to produce a census of digital marketing circuits independent of the large distribution networks in Rio de Janeiro in 2021 and 2022, focusing on those that mobilize principles of sustainability in their communication. After characterizing their organization and the aspects of sustainability they invoke, we conducted semi-structured interviews on initiatives whose main role is to act as a commercial intermediary. The data obtained contributed to the distinction of different profiles of circuits in the city and discuss the potential and limits of digital tools to foster sustainable food systems.